Peran Komunikasi Interpersonal Perawat Dengan Pasien Instalasi Gawat Darurat (IGD) Dalam Pertolongan Pertama Rsud M.Natsir Kota Solok - Dafina Mutiara Fefrans; Ria Edlina (CV. ITTC INDONESIA, 2025)
This research was conducted to analyze the role of interpersonal communication between nurses and patients in the Emergency Room (IGD) of the Mohammad Natsir Regional General Hospital, Solok City with a focus on first aid and its impact on patient satisfaction. Interpersonal communication theory according to Joseph A. Devito was used as the basis for this research. The research method applied is descriptive qualitative, with data collection techniques through interviews, observation and documentation. The research results show that effective interpersonal communication between nurses and emergency room patients is implemented through five main aspects: (1) Openness, where nurses create conditions that allow patients to talk openly about their complaints; (2) Empathy, where the nurse shows attention and concern for the patient; (3) Support, which is realized by nurses accepting ideas and suggestions from patients; (4) Positive feelings, which nurses build to increase patient enthusiasm, determination and confidence; and (5) Equality, where nurses treat patients fairly and humanely. This research confirms the importance of interpersonal communication in improving the quality of first aid in the ER, as well as playing a significant role in increasing patient satisfaction.